Nano-pesticides: the lunch-box principle—deadly goodies (semio-chemical functionalised nanoparticles that deliver pesticide only to target species) - Scott-Fordsmand, J. J.; Fraceto, L. F. [UNESP]; Amorim, M. J.B. (Springer Nature, 2022)
Nature contains many examples of “fake promises” to attract “prey”, e.g., predatory spiders that emit the same sex-attractant-signals as moths to catch them at close range and male spiders that make empty silk-wrapped gifts in order to mate with a female. Nano-pesticides should ideally mimic nature by luring a target and killing it without harming other organisms/species. Here, we present such an approach, called the lunch-box or deadly-goodies approach. The lunch-box consists of three main elements (1) the lure (semio-chemicals anchored on the box), (2) the box (palatable nano-carrier), and (3) the kill (advanced targeted pesticide). To implement this approach, one needs to draw on the vast amount of chemical ecological knowledge available, combine this with recent nanomaterial techniques, and use novel advanced pesticides. Precision nano-pesticides can increase crop protection and food production whilst lowering environmental impacts. Graphical Abstract: [Figure not available: see fulltext.]